The contribution of services liberalization to poverty reduction : what role for the GATS? - Adlung, Rudolf (WTO GenevaCH, 2007)
Traces various (potential) links between services liberalization and poverty alleviation. Looks at the role GATS could play in opening services markets and/or securing liberal access regimes.